2003
DOI: 10.3354/meps250081
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of extracellular polymers of Phaeocystis globosa and P. antarctica

Abstract: Extracellular polymers of Phaeocystis globosa and P. antarctica were characterized by elemental analysis, X-ray photoelectron spectroscopy (XPS), and matrix-assisted laser desorption ionization-time of flight-mass spectrometry (MALDI-TOF-MS) analysis. The 2 species were grown in axenic and bacterized cultures to examine the effect of bacterial degradation on the composition of the extracellular polymers. The C:N ratios for extracellular polymers from P. globosa and P. antarctica grown under these conditions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 41 publications
(62 reference statements)
1
24
2
Order By: Relevance
“…Qualitative staining of the colony matrix indicated the absence of lipophilic compounds and chitin, but the presence of amino groups (Hamm et al 1999). Matrix-assisted laser desorption/ionization (MALDI) analysis showed that N was not proteineous, but probably present in aminosugars (Solomon et al 2003). The presence of the aminosugar sialic acid was confirmed by aminolabeling .…”
Section: Mucopolysaccharidesmentioning
confidence: 85%
See 2 more Smart Citations
“…Qualitative staining of the colony matrix indicated the absence of lipophilic compounds and chitin, but the presence of amino groups (Hamm et al 1999). Matrix-assisted laser desorption/ionization (MALDI) analysis showed that N was not proteineous, but probably present in aminosugars (Solomon et al 2003). The presence of the aminosugar sialic acid was confirmed by aminolabeling .…”
Section: Mucopolysaccharidesmentioning
confidence: 85%
“…Since all studies used filtration techniques applying pressure, it is most likely that the DOM also contained mucopolysaccharides. The overall C/N ratio of the DOM is low, around 7 (Biddanda and Benner 1997; Solomon et al 2003). Similar to mucopolysaccharides, extracolonial polymers self assemble in hydrated polymer gels on a time scale of approximately two days (Solomon et al 2003).…”
Section: Contribution Of Mucopolysaccharides-c To Pocmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we assessed the abundance and the contribution of major bacterial groups to DOM assimilation. We examined the assimilation of amino acids, glucose, protein, and EPS because of the biogeochemical importance of these compounds in all aquatic environments, including cold ones (Kirchman et al 2001, Krembs et al 2002, Solomon et al 2003. The concentrations of glucose and amino acids vary regionally in the Arctic Ocean, and both compounds have high turnover rates, but amino acid uptake has exceeded glucose uptake in the Arctic waters examined to date (Rich et al 1997, Meon & Amon 2004.…”
mentioning
confidence: 99%
“…In the current work however, early algal concentrations are all set to a single low value. Phaeocystis is included because its life history is specialized with regard to the organics -it is known for release of organosulfur compounds, polysaccharides and amino sugars [118,[131][132]. Polymer chemistry allows this unique organism to become effectively multicellular by forming colonies.…”
Section: Appendix B: Parametersmentioning
confidence: 99%